Innovative solutions to address the humanitarian-development nexus : Review of the pilot introduction of the Blended Approach at GOAL - Murphy, Susan; Robert, Mariana; Devine, Catherine (goalglobal.org, 2020)
In 2018 GOAL received support from the Department Foreign Affairs and Trade (DFAT), Irish Aid, to pilot a new funding modality – the “blended approach” - intended to bridge the humanitarian-development divide through closer collaboration and stronger interoperability between humanitarian and development interventions. This study conducts a review of this pilot, examining the experiences of GOAL staff in transitioning to this new model, and exploring its effect on programming, monitoring, evaluating, learning and reporting. As noted by the Organisation for Economic Co-operation and Development (OECD 2020), DFAT are a trusted and proactive development partner, committed to improving the efficiency and effectiveness of the development programmes it supports. DFAT have long standing relations with GOAL and a deep understanding of the GOAL approach to development cooperation and humanitarian action. On the basis of this relationship and the recognition of the need for innovation in this space, the aim of the pilot is to test a “blended approach” which supports humanitarian and development practitioners in building the resilience of fragile communities and developing sustainable and context-relevant solutions for communities supported by GOAL. The purpose of this review report is two-fold. Firstly, it is intended to provide DFAT with insights into use of the “blended approach”, and its suitability for wider deployment. Secondly, it documents the learning from the pilot for sharing both internally in GOAL, and externally, with other agencies and organisations in the sector. The review and subsequent report emerged following seven key stages – research design; rapid rigorous literature review; primary data collection and analysis; report drafting; report review and feedback collection with participants; revisions; delivery of final report to GOAL Senior Management Team (SMT) for engagement with DFAT. The review utilised and adapted OCED development effectiveness indicators to form the basis of the analytical framework. It focused on two key questions: Firstly, what are the effects of the “blended approach” on GOAL’s operations in the following areas – relevance; efficiency; effectiveness; and sustainability. Secondly, it examined if the type of programme, country context and organisation influence the effects of the “blended approach”? In relation to the first question, the findings indicate that a transition to the “blended approach” offers a strong possibility to enhance and deepen the relevance, efficiency, effectiveness, and sustainability of GOAL programming over time. Most specifically, the areas of joint programming and flexible funding allow for significantly more adaptable forms of responding to context-specific needs. The time-saving potential of unified reporting, monitoring, evaluation, and learning systems was also noted as a key benefit of this shift, enabling greater efficiency in the design, planning, and management of programmes. However, the review finds that further efforts are required to embed this way of working and thinking into project design, monitoring, evaluating, reporting and learning structures to reap the full benefits offered by this approach. Further findings relating to the second question suggest that this approach is most suited to operations in complex and fragile contexts. It highlights how understanding the context is paramount to the success of the “blended approach” as a vehicle for more effective programming as fragile contexts, areas of acute crises and conflict, as well as areas with high numbers of Internally Displaced People (IDPs) and refugees, require flexibility and adaptability. In addition, the research found that the “blended approach” is best implemented by an organization that is agile and highly adaptable. The approach therefore does not cohere well with all organisational structures, ethos, and approaches to practice. Thus, careful consideration is required of where to apply this approach and which organisations are best placed to maximise the opportunities afforded by this new way of working. The report presents case studies that illustrate how the “blended approach” is being used in practice in GOAL programme countries funded by DFAT, Irish Aid. Overall, the findings indicate that the “blended approach” successfully facilitated GOAL operations in navigating the humanitarian-development nexus through critically understanding the context, joint programming, and flexible funding, as well as prioritising resilience and sustainability. The report concludes with an overview of the key challenges and recommendations including that staff should be given clear guidance on how to implement, monitor and evaluate the “blended approach, as well as ley lessons learned for future implications of this approach.
Keywords: International Development; Humanitarian innovation; Sustainable Development Practice; Development; Justice and safeguarding; Policy; Poverty